A novel synergistic method on potential green and high value-added utilization of blast furnace slag. (20th December 2021) - Duan, Wenjun; Wang, Diguang; Wang, Zhimei; Zhan, Yaquan; Mu, Tongtong; Yu, Qingbo
Abstract: In order to utilize blast furnace slag resource at low cost, pollution-free, refinement and high value-added, a novel technical route was proposed to collaboratively produce zeolite and hydrotalcite-like compound. In this study, the changing property of slag in the treatment process was investigated and the thermodynamic and kinetic analyses of the leaching reaction were conducted to prove its feasibility. The silica gel and residue liquid were separated effectively from the slag. Then, 13X zeolite and hydrotalcite-like compound were successfully synthesized from water quenching blast furnace slag using hydrochloric acid treatment followed by hydrothermal method and co-precipitation method. The successful formation of 13X zeolite and hydrotalcite-like compound were obtained effectively with good surface morphology and crystal structure. Mass balance of the blast furnace slag utilization process was established. Meanwhile, these two samples exhibited good behavior of CO2 adsorption capacity and enjoyed a promising market prospect. The maximum adsorption capacities of 13X zeolite and hydrotalcite-like compound were 116.48 mg g −1 at 313 K and 149.63 mg g −1 at 873 K, respectively. Finally, the preliminary economic evaluation of the integrated system was conducted, and the economic benefit of 1 kg slag was about 1.281 $. Graphical abstract: Image 1 Highlights: A novel resource utilization method of the blast furnace slag was proposed. 13X zeolite and hydrotalcite-like compounds could be produced collaboratively. The technology prototype combined slag utilization and CO2 sequestration was established. The new technology achieves the objective of high value-added resources production.